Kids array - Abdul Razak, Mariatulqabtiah; Mat Isa, Nurulfiza; Saidi, Noor Baity (Universiti Putra Malaysia Press, 2015)
Children have limitless imagination, and drawing can be one the ways in which they can be creative. In order to compare the effect of psychology and environment, between urban and rural children, forty 10-year-old schoolchildren were assigned to draw their interpretation of “bird” on a long paper scroll. A drawing could reveal how children feel about their environment. Interestingly, the patterns of drawing of each group were relatively consistent. A majority of female schoolchildren from urban school drew imaginative forms of bird, flying freely.